Task-dependent evaluative processing of moral and emotional content during comprehension: an ERP study - Kunkel, Angelika; Filik, Ruth; Mackenzie, Ian Grant; Leuthold, Hartmut (Springer, 2018)
Recently, we showed that when participants passively read about moral transgressions (e.g., adultery) they implicitly engage in the evaluative (good–bad) categorization of incoming information, as indicated by a larger event-related brain potential (ERP) positivity to immoral than moral scenarios (Leuthold, Kunkel, Mackenzie, & Filik, 2015). Behavioral and neuroimaging studies indicated that explicit moral tasks prioritize the semantic-cognitive analysis of incoming information but that implicit tasks, as used in Leuthold et al. (2015), favor their affective processing. Therefore, it is unclear whether an affective categorization process is also involved when participants perform explicit moral judgments. Thus, in two experiments, we used similarly constructed morality and emotion materials for which their moral and emotional content had to be inferred from the context. Target sentences from negative vs. neutral emotional scenarios and from moral vs. immoral scenarios were presented using rapid serial visual presentation. In Experiment 1, participants made moral judgments for moral materials and emotional judgments for emotion materials. Negative compared to neutral emotional scenarios elicited a larger posterior ERP positivity (LPP) about 200 ms after critical word onset, whereas immoral compared to moral scenarios elicited a larger anterior negativity (500-700 ms). In Experiment 2, where the same emotional judgment to both types of materials was required, a larger LPP was triggered for both types of materials. These results accord with the view that morality scenarios trigger a semantic-cognitive analysis when participants explicitly judge the moral content of incoming linguistic information but an affective evaluation when judging their emotional content.